2017
DOI: 10.1016/j.oraloncology.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral health affects survival in head and neck cancer

Abstract: Introduction Poor oral health has emerged as a risk factor for squamous cell carcinoma of the head and neck (HNSCC) but its impact on survival has not been examined. We sought to estimate the impact of oral health indicators on survival in a population-based HNSCC cohort. Materials and Methods Cases (n=1381) and age-, sex- and race-matched controls (n=1396) were participants in the Carolina Head and Neck Cancer Epidemiologic Study (CHANCE). Vital status was determined via linkage with the National Death Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 50 publications
4
99
0
Order By: Relevance
“…Poor oral status, detected by a validated oral screening tool, is associated with age‐related outcomes, such as malnutrition, physical dependency, dysphagia and sarcopenia, in hospitalized older adults . Furthermore, poor oral hygiene is associated with mortality among healthy adults, middle‐aged male adults, institutionalized older adults, dialysis patients, and patients with head and neck cancer . Furthermore, poor oral status is common and associated with high mortality among patients with pneumonia in hospitals and nursing homes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor oral status, detected by a validated oral screening tool, is associated with age‐related outcomes, such as malnutrition, physical dependency, dysphagia and sarcopenia, in hospitalized older adults . Furthermore, poor oral hygiene is associated with mortality among healthy adults, middle‐aged male adults, institutionalized older adults, dialysis patients, and patients with head and neck cancer . Furthermore, poor oral status is common and associated with high mortality among patients with pneumonia in hospitals and nursing homes .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Furthermore, poor oral hygiene is associated with mortality among healthy adults, 3 middle-aged male adults, 4 institutionalized older adults, 5 dialysis patients, 6 and patients with head and neck cancer. 7 Furthermore, poor oral status is common and associated with high mortality among patients with pneumonia in hospitals and nursing homes. 8 Oral health management is thus an important social issue to consider, particularly given the increase in the older population.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 The psychological distress and poor oral health were negatively related with time, because of the diagnoses of cancer, 3 , 5 treatment, 4 , 6 and poor prognosis in cancer patients. 7 , 8 In Saudi Arabia, due to a wide array of national screening programs and diagnosis of new cancer cases at an early stage, 9 the survival rate among cancer patients continues to increase. 10 This necessitates routine assessment and intervention among cancer survivors to maintain quality of life 11 , 12 and better health management and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This positive association can partly be explained by prior studies that show positive associations between periodontal disease and various chronic and severe diseases 8–10. Other studies also find that the frequency of toothbrushing and the use of secondary oral hygiene products are associated with diseases such as hypertension, diabetes mellitus, cardiovascular disease, and head and neck cancers 11–14. In a recent study, researchers found that flossing and brushing of interdental spaces may reduce the risk for new cardiovascular events among patients with coronary heart disease 24.…”
Section: Discussionmentioning
confidence: 95%
“…For example, studies show associations between periodontal disease and a higher risk of Alzheimer’s disease, coronary heart disease, rheumatoid arthritis, glomerulonephritis, inflammatory bowel disease and prostate cancer 8–10. Other studies show that poor oral hygiene is associated with hypertension, diabetes mellitus, cardiovascular disease, and head and neck cancers 11–14. Still other studies have found a positive association between poor oral health and mortality 4 7 15…”
Section: Introductionmentioning
confidence: 99%